The Electrification of the World - Baldwin, Ian (Advances in Social Sciences Research Journal, 2023)
It is unlikely there is a more momentous event in the creation of modern civilization than the invention of the electric light and its handmaiden, the worldwide grid. The 21st century Green Economy rests firmly on the foundation of the electric grid. Few know that the dynamo, the electric light – both arc and incandescent – and the electric grid were invented and launched in the late 1870s and early 1880s. This essay describes how and why these inventions happened. It is divided into two parts, each with its separate references, for the sake of clarity, as a great many important discoveries and technicalities had to be worked out each step of the way. Part One covers the development of the arc lamp and its “engine,” the dynamo. Part Two covers the invention of the long-burning carbon-based filament of the incandescent light bulb, as well as more powerful dynamos to supply power to thousands and soon millions of these new bulbs, and Edison’s visionary and pioneering construction of the revolutionary first electric grid. These developments seeded the construction of the universal worldwide grid in the 1890s and early 20th century. Their origins and history are integral to understanding the basis of our 21st century material civilization.